Pseudo Sliding Plane in Super-Thick Soil Materials Deposit at Ngasinan Deep Landslide Area - Purnamasari, Anastasia Neni Candra; Sartohadi, Junun; Hartantyo, Eddy (Revista Brasileira de Geomorfologia, 2024)
The research focuses on analyzing landslides within an area abundant in varying sizes of these occurrences. The research is being conducted in Ngasinan, Bogowonto watershed area in Indonesia. These landslides happened in the consistently loose, deep volcanic sediment, referred to as soil material, over 10 meters thick. The goal of this research is to assess potential sliding plane triggering these landslides within this soil material. To achieve this, a blend of geophysical and soil science methodologies is applied. Geophysical measures, specifically resistivity parameters, discern distinctions within the layers of soil material, determined through geoelectric methods. Additionally, soil science factors like Cation Exchange Capacity (CEC) and dispersing ease are used to evaluate the layers with pseudo-sliding plane. Findings demonstrate varied resistivity values, CEC, and water content across the different material layers. The N1 layer, situated at a 5-meter depth, exhibiting characteristics of 5Y 8/1 color (white), shows a resistivity of 8.7 Ωm, a CEC of 54 meq/100g, and high dispersible. Identified as a potential cause of initial landslides or sliding planes, the N1 layer's distinctive values in resistivity, CEC, and water content validate it as an area of concern for potential landslides. These findings confirm that differences in these factors can serve as an early identification for potential landslide-prone areas.